Rituximab versus azathioprine in maintenance therapy of patients with granulomatosis with polyangiitis - Samira Alesaeidi; Masoud Radnia; Soheil Tavakolpour; Seyed Behnam Jazayeri; Shima Loni (Caspian Journal of Internal Medicine)
Background: Granulomatosis with polyangiitis (GPA) is a rare disease affecting medium-small vessels, causing granuloma formation and inflammation. This study aimed to assess the efficacy and safety of RTX versus Azathioprine (AZA) for maintenance treatment in GPA patients. Methods: This retrospective cohort study involved a review of medical records of recently diagnosed GPA patients undergoing maintenance treatment with RTX or AZA. The main variable was the frequency of relapses within an 18-month follow-up period. Additionally, the study compared changes in BVAS.WG score (The Birmingham Vasculitis Activity Score-Wegner specific) and Damage (vasculitis damage index (VDI)), mortality, and treatment complications between the two groups. Results: Among the 43 patients receiving RTX maintenance treatment, 8 (18.6%) experienced relapses during 24 months follow-up, while 14 (66.6%) out of the 21 patients receiving AZA relapsed (Hazard Ratio = 6.9 and 95% confidence interval = 1.95-19.3, p <001). Notably, the increase in the BVAS-WG score was significantly lower in the RTX group compared to the AZA group (p <001). The cumulative steroid dose was 143±21 mg in the RTX group and 125±25 mg in the AZA group (P = 0.1). Treatment side effects were similar in both groups (p >0.05). Conclusion: Maintenance treatment with RTX is associated with better treatment response and lower relapse rate compared to AZA. There was no difference in treatment complications between AZA or RTX in maintenance treatment.